2017
DOI: 10.1080/13691058.2016.1272715
|View full text |Cite
|
Sign up to set email alerts
|

Abortion attitudes among South Africans: findings from the 2013 social attitudes survey

Abstract: Abortion is legal in South Africa, but over half of abortions remain unsafe there. Evidence suggests women who are (Black) African, of lower socioeconomic status, living with HIV, or residents of Gauteng, KwaZulu-Natal, or Limpopo provinces are disproportionately vulnerable to morbidity or mortality from unsafe abortion. Negative attitudes toward abortion have been documented in purposively sampled studies, yet it remains unclear what attitudes exist nationally or whether they differ across sociodemographic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…For black women in South Africa, abortion's social stigma and racial discrimination in health services are also determinants for postponing use of services, one of the factors resulting in the high rate of unsafe abortion and in the search for abortion services at later stages in the pregnancy 23,24 , corroborating our study's results. In the United States, black and Latina women suffer discrimination and stigma in health services even during spontaneous abortion, jeopardizing their search for care 39 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For black women in South Africa, abortion's social stigma and racial discrimination in health services are also determinants for postponing use of services, one of the factors resulting in the high rate of unsafe abortion and in the search for abortion services at later stages in the pregnancy 23,24 , corroborating our study's results. In the United States, black and Latina women suffer discrimination and stigma in health services even during spontaneous abortion, jeopardizing their search for care 39 .…”
Section: Discussionsupporting
confidence: 88%
“…International studies, primarily in the United States and South Africa, show a similar situation for black women in the search for abortion services, although their jurisdictions allow abortion. Namely, transportation logistics and financial resources for reaching and having the procedure performed are also factors that limit access in the U.S. and South Africa 20,21,22,23,31 . In Brazil, universal coverage by the Brazilian Unified National Health System (SUS) means that the financial factor is limited essentially to access to urban transportation, mainly by spatial segregation, where poor people live in the more peripheral urban areas that lack public services, including healthcare services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that for each category of increased education, respondent abortion attitudes are, on average, more favorable, for example, with a nearly a one-point increase (B=0.831) in abortion attitudes among university educated respondents to those with no formal education. Others have reported more accepting abortion attitudes with higher levels of education (Mosley et al 2017). Additionally, religiosity and abortion attitudes has been widely studied (Adamczyk and Valdimarsdóttir 2018;Patel and Johns 2009;Barkan 2014;Begun et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, factors that may affect a person’s belief in the permissibility of abortion include fetal age/development, risk to the pregnant person, whether the pregnant person’s partner or family agrees with the termination, and pregnancy from rape or incest (Hans & Kimberly, 2014; Jozkowski et al, 2018). Conservative and traditional Christian religious beliefs, strong beliefs about gender role traditionality, and benevolent sexism have all been found to be highly related to negative abortion attitudes (Huang et al, 2016; Mosley et al, 2017). The intersections of a person’s identities may also create complex values surrounding abortion; for instance, a person who belongs to a conservative religious group and also identifies as feminist may experience conflict stemming from their ideological backgrounds.…”
Section: The Proposed Pdmmmentioning
confidence: 99%